Dom Baca: capstone - Baca, Dom, artist (Colorado State University. Libraries, 2021)
The artist's statement: My journey as an artist can be explained in three similar words, Communication, Community and Computers. Visual arts to me has always been like standing on a stage with a megaphone in front of a crowd of people. Design is a way to communicate with others and connect with them emotionally. When I first began my journey as an artist, I didn't quite know what to say. With limitless possibilities and an unknown number of listeners, I often questioned what I wanted to communicate through my art. In recent years, I have begun to find my voice in standing up for what I believe in and that at its core is creating community. I have used my art to fuel my passion for standing up against the oppressions and injustices we see in the world today in the hopes it will educate others to help make change. I believe when we have equality and equity within our society, we will be able to thrive as a community. Since then my interest has grown and I found my message to communicate, my next step was to find my megaphone, also known as my medium. I began to learn how people communicate online in virtual spaces with the changing digital world. This has led me to explore more electronic and computer-based arts such as graphic design and the electronic arts. I am interested in the aesthetics, functionality and the ease of communication working with computers brings. Within my personal explorations as an artist I am constantly looking for ways to communicate my message with the audience while hoping that it will spark a conversation of their own. I believe the best artwork is work that gets people talking. As of right now, I am experimenting with virtual clothing and its effects on our online personas. Within my work I have been digitally modeling clothes and working on ways to bring them to life by mixing them with digital photography as well as augmented reality software. Within this I am looking at ways we can change our online appearance and what that means in relation to those around us within online spaces. In my work I am always looking to spark up a conversation. When working with clients to help bring their visual messages to life, I always try to use my knowledge of design to help effectively communicate their messages and the emotional undertones behind them. I am an active listener who understands the importance of the client's voice within the project. I always see through that the client's vision, passion, and messages are the center focal point throughout the design process. Additionally, I find it important to make sure that I am transparent and explain my process thoroughly, so the client feels involved and welcomed within the design process. I see the project through to completion and I always give an expected timeline, so there is always transparency within the design process.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art